Undocumented Migration, Xenophobia and The Struggle for Employment in South Africa - Victor H Mlambo; Xolani Thusi; Mandisa Sunshine Melanie Makhathini; Sbonelo Gift Ndlovu; Muzi Shoba (JISR Management and Social Sciences & Economics, 2023)
This paper highlights the issues associated with undocumented immigration and xenophobic attacks directed at African immigrants in South Africa. The paper employs the scapegoat theory to interrogate the phenomenon under study. This paper solely relies on secondary data. It employs a narrative literature review as a research methodological approach. The paper argues that xenophobic attacks on African immigrants are a consequence of a combination of policy failures in South Africa, and African immigrants, due to their situation (of being undocumented), become easy scapegoats for such policy failures in the country. The paper concludes that the government needs to foster a collaborative approach to address the problem of xenophobia in South Africa. Even though issues such as poverty, inequality, and unemployment contribute to the xenophobic sentiments directed at undocumented migrants, cooperation between various stakeholders will go a long way in reducing tensions between locals and migrants. At the center of this has to be economic growth. However, growth alone will not suffice. There is a need for a concentrated advocacy campaign to help better build communication avenues between locals and foreign nationals; this is key to building a cohesive social environment.